Effect of Oily and Watery Extracts of Rosmarinus officinalis as Preservative in Minced Meat - Abid, Majid M. (The Iraqi Journal of Veterinary Medicine, 2011)
The effect of various concentration of Rosmarinus officinalis on the total count of bacteria in minced meat stored at temperature between 4 – 6oC for periods up to 14 days is examined. The results showed that the oily extract at the concentration of 20 – 100 mg/ml and the watery extract of the concentration of 120 – 200 mg/gm have a significant effect (P<0.05) in comparison with blank treatment No significant variation ware found at (P<0.05) in the treatment with the watery and oily extracts